Bridging the livestock feed gap with improved feeds - International Livestock Research Institute (International Livestock Research Institute, 2021)
Farm animals are critical for human development. In Ethiopia livestock contributes up to 46% of the country’s agricultural GDP and the need for sustainable livestock feeds is high in many parts of the country. This film highlights the works of Africa RISING in helping smallholder farmers to increase forage production in a sustainable way and meet the feed demand. More information: https://africa-rising.net/